Membentuk Karakter Kepemimpinan Remaja di Era Revolusi Industri 4.0 - Nanang Djamaludin (Jurnal Pustaka Dianmas, 2021)
The development of the industrial revolution today is increasingly encouraging technological developments to become more advanced. One of the characteristics of the 4.0 industrial revolution is the interconnection between humans and machines / devices through the internet of things / internet of people. The Digital Age is currently taking place and moving so fast towards new points of achievement that have never happened before. The result of this is the result of many terrible changes taking place in society. In fact, not a few things in society are uprooted (disruption). With this activity. Youth leadership as Generation Z today, who also live side by side with generations above and below it, must truly understand the challenges, threats and opportunities that are provided today. While preparing himself and actually activating the potential for superior and authentic qualities that are contained within him.